Single-Ended Protection Scheme for Offshore Flexible Low-Frequency Transmission Lines Based on High-Frequency Transient Quantities - LI Jingzheng, DU Xiaotong, LI Meng (Dianli jianshe)
[Objective] To enhance the speed and reliability of protection for marine flexible low-frequency AC transmission lines and ensure the safe operation of offshore wind power flexible low-frequency AC transmission systems，high-frequency transient single-ended fast protection considering the boundary effects of busbars and modular multilevel matrix converters（M3Cs）is proposed. [Methods] By analyzing the equivalent models of busbars and M3Cs at both ends of the line，the boundaries at both ends were noted to have a significant attenuation effect on the high-frequency components of voltage traveling waves，and a clear high-frequency range was determined. The differences in the forward and backward wave high-frequency components under various time conditions for internal and external faults were revealed. Based on this，a successive mode decomposition algorithm was used to extract high-frequency transient components，characterizing the distinction between the internal and external faults through the ratio of forward to backward wave high-frequency energies. [Results] The PSCAD/EMTDC simulation results showed that the successive mode decomposition algorithm effectively extracted high-frequency information from noisy data. The proposed single-ended protection scheme accurately and reliably identified the internal and external faults within 2 ms，tolerating up to 10 dB noise and 500 Ω transition resistance，demonstrating superior resistance to transition resistances and noise compared to traditional single-ended transient-based protection methods. [Conclusions] The boundaries of marine flexible low-frequency AC transmission lines exhibit a significant attenuation effect on signals with frequencies greater than 5 kHz. For internal versus external faults，the energy values of the fault backward and forward wave high-frequency components are notably different，leading to a significantly faster action speed of the constructed protection method compared to existing differential protection schemes. This method does not require communication conditions and can withstand the impact of the marine environment，thus showing potential for engineering applications.